Influence of verapamil on the pharmacokinetics of oridonin in rats - Jing Liu (Taylor & Francis Group, 2019)
Context: Oridonin has been traditionally used in Chinese treatment of various cancers, but its poor bioavailability limits its therapeutic uses. Verapamil can enhance the absorption of some drugs with poor oral bioavailability. Whether verapamil can enhance the bioavailability of oridonin is still unclear. Objective: This study investigated the effect of verapamil on the pharmacokinetics of oridonin in rats and clarified its main mechanism. Materials and methods: The pharmacokinetic profiles of oral administration of oridonin (20 mg/kg) in Sprague-Dawley rats with two groups of six animals each, with or without pre-treatment of verapamil (10 mg/kg/day for 7 days) were investigated. The effects of verapamil on the transport and metabolic stability of oridonin were also investigated using Caco-2 cell transwell model and rat liver microsomes. Results: The results showed that verapamil could significantly increase the peak plasma concentration (from 146.9 ± 10.17 to 193.97 ± 10.53 ng/mL), and decrease the oral clearance (from 14.69 ± 4.42 to 8.09 ± 3.03 L/h/kg) of oridonin. The Caco-2 cell transwell experiments indicated that verapamil could decrease the efflux ratio of oridonin from 1.67 to 1.15, and the intrinsic clearance rate of oridonin was decreased by the pre-treatment with verapamil (40.06 ± 2.5 vs. 36.09 ± 3.7 µL/min/mg protein). Discussion and conclusions: These results indicated that verapamil could significantly change the pharmacokinetic profile of oridonin in rats, and it might exert these effects through increasing the absorption of oridonin by inhibiting the activity of P-gp, or through inhibiting the metabolism of oridonin in rat liver. In addition, the potential drug–drug interaction should be given special attention when verapamil is used with oridonin. Also, the dose of oridonin should be carefully selected in the clinic.